2003
DOI: 10.1001/archpsyc.60.9.978
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Antidepressant Medication Treatment and Suicide in Adolescents

Abstract: An inverse relationship between regional change in use of antidepressants and suicide raises the possibility of a role for using antidepressant treatment in youth suicide prevention efforts, especially for males, older adolescents, and adolescents who reside in lower-income regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
2
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(183 citation statements)
references
References 44 publications
8
157
2
16
Order By: Relevance
“…The lower bound of this confidence interval suggests that an increase in SSRI sales in Sweden equal to 13 percent over 1999 or 2000 levels (about two defined daily doses per capita) could reduce suicide rates by up to 2.6 percent, consistent with the estimate presented above from our panel of country-level data. The magnitude of our estimate is significantly smaller than what is presented in the study of adolescent suicides by U.S. ZIP code area by Olfson et al (2003), but as noted above we have significant concerns about the key explanatory variable of interest used in their study. els.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The lower bound of this confidence interval suggests that an increase in SSRI sales in Sweden equal to 13 percent over 1999 or 2000 levels (about two defined daily doses per capita) could reduce suicide rates by up to 2.6 percent, consistent with the estimate presented above from our panel of country-level data. The magnitude of our estimate is significantly smaller than what is presented in the study of adolescent suicides by U.S. ZIP code area by Olfson et al (2003), but as noted above we have significant concerns about the key explanatory variable of interest used in their study. els.…”
Section: Discussionmentioning
confidence: 57%
“…Olfson et al (2003) focus on changes between 1985-89 and 1995-99 in suicide rates to adolescents within three-digit ZIP code regions. They find that suicide rates for children 10-19 decline more in regions that experience a relatively greater increase in the "antidepressant medication treatment rate," defined as the num- , 1950-2000.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, between 1985 and 1999, the suicide rate in the US decreased from 12.4 to 10.7 per 100,000, while the prescription of AD (predominantly SSRI) was quadrupled 42 . In North American teenagers, for every 1% increase in AD prescription, there was a decrease of 0.23 suicides per 100,000 annually (p < 0.001) 43,44 . Additionally, the 13% increase in SSRI sales in 27 countries during 1999 reduced suicide rates by 2.5% in those countries.…”
Section: Usage Of Antidepressants and Decrease In Suicidal Ratesmentioning
confidence: 97%
“…Depressive illness is associated with great personal suffering, an increased risk of suicide and most sufferers will experience at least one recurrence during their life time. At a population level several studies have reported an association between increasing antidepressant use and a reduction in suicide rates, though the potential effect of confounders makes it impossible to prove that this is a causal relationship (Henriksson and Isacsson, 2006;Olfson et al, 2003). Antipsychotic drugs have proven efficacy in the acute (Davis et al, 2003) and long-term treatment of schizophrenia (Leucht et al, 2003b) and the treatment of mania (Perlis et al, 2006).…”
Section: Avoiding Adverse Effectsmentioning
confidence: 99%